To Regulate or Not to Regulate: Assimilation of Dietary Fatty Acids in the Temperate Copepod Temora longicornis - Franco-Santos, Rita M.; Auel, Holger; Boersma, Maarten; De Troch, Marleen; Graeve, Martin; Meunier, Cédric Leo; Niehoff, Barbara (Frontiers in Marine Science, 2022)
Consumer regulation of lipid composition during assimilation of dietary items is related to their ecology, habitat, and life cycle, and may lead to extra energetic costs associated with the conversion of dietary material into the fatty acids (FAs) necessary to meet metabolic requirements. For example, lipid-rich copepods from temperate and polar latitudes must convert assimilated dietary FAs into wax esters, an efficient type of energy storage which enables them to cope with seasonal food shortages and buoyancy requirements. Lipid-poor copepods, however, tend to not be as constrained by food availability as their lipid-rich counterparts and, thus, should have no need for modifying dietary FAs. Our objective was to test the assumption that Temora longicornis, a proxy species for lipid-poor copepods, does not regulate its lipid composition. Isotopically-enriched (13C) diatoms were fed to copepods during a 5-day laboratory experiment. Compound-specific stable isotope analysis of algae and copepod samples was performed in order to calculate dietary FA assimilation, turnover, and assimilation efficiency into copepod FAs. Approximately 65% of the total dietary lipid carbon (C) assimilated (913 ± 68 ng C ind-1 at the end of the experiment) was recorded as polyunsaturated FAs, with 20 and 15% recorded as saturated and monounsaturated FAs, respectively. As expected, T. longicornis assimilated dietary FAs in an unregulated, non-homeostatic manner, as evidenced by the changes in its FA profile, which became more similar to that of their diet. Copepods assimilated 11% of the total dietary C (or 40% of the dietary lipid C) ingested in the first two days of the experiment. In addition, 34% of their somatic growth (in C) after two days was due to the assimilation of dietary C in FAs. Global warming may lead to increased proportions of smaller copepods in the oceans, and to a lower availability of algae-produced essential FAs. In order for changes in the energy transfer in marine food webs to be better understood, it is important that future investigations assess a broader range of diets as well as lipid-poor zooplankton from oceanographic areas throughout the world’s oceans.